2002
DOI: 10.4049/jimmunol.169.3.1365
|View full text |Cite
|
Sign up to set email alerts
|

The Rap GTPases Regulate B Cell Migration Toward the Chemokine Stromal Cell-Derived Factor-1 (CXCL12): Potential Role for Rap2 in Promoting B Cell Migration

Abstract: Stromal cell-derived factor-1 (SDF-1) is a potent chemoattractant for B cells and B cell progenitors. Although the binding of SDF-1 to its receptor, CXCR4, activates multiple signaling pathways, the mechanism by which SDF-1 regulates cell migration is not completely understood. In this report we show that activation of the Rap GTPases is important for B cells to migrate toward SDF-1. We found that treating B cells with SDF-1 resulted in the rapid activation of both Rap1 and Rap2. Moreover, blocking the activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 43 publications
6
101
0
Order By: Relevance
“…39,40 We thus tested whether silencing of FAK affects CXCL12-induced Rap1 activation. In agreement with previous reports on CXCL12-induced Rap1 activation in hematopoietic cells, 40,41 we show that CXCL12 induced Rap1 activation in CTR-RNAi cells (Figure 3d) and in intact REH cells (not shown).…”
Section: Decreased Cxcl12-induced Rap1 Activation In Fak-deficient Cellssupporting
confidence: 82%
“…39,40 We thus tested whether silencing of FAK affects CXCL12-induced Rap1 activation. In agreement with previous reports on CXCL12-induced Rap1 activation in hematopoietic cells, 40,41 we show that CXCL12 induced Rap1 activation in CTR-RNAi cells (Figure 3d) and in intact REH cells (not shown).…”
Section: Decreased Cxcl12-induced Rap1 Activation In Fak-deficient Cellssupporting
confidence: 82%
“…Rap1 is known to stimulate integrin activation, cytoskeleton rearrangements, and cell polarization both in the presence and absence of a chemokine gradient. 42,43 We observed that Rap1a and Rap1b depletion abolished the migratory advantage of MEC1-CD38H cells. This indicates that Rap1 activity contributes to the increased migration and adhesion linked to CD38 expression.…”
Section: Discussionmentioning
confidence: 74%
“…30 SDF-1 is a chemokine that plays an important role in B-cell development, trafficking, and activation. [8][9][10][11] Several studies suggested that SDF-1 may have a crucial role in the development of autoimmune disease. Matin et al 31 demonstrated that the chemokine SDF-1 may be an essential chemoattractant in trafficking and migration of mature autoreactive B cells from bone marrow to the periphery or inflammatory sites in the development of autoimmune diabetes.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
“…8 It is a chemoattractant for monocytes, naive and memory T lymphocytes, and B lymphocytes. [9][10][11] SDF-1 is also a costimulatory factor for CD4 þ T-lymphocyte activation. 12 In view of the presence of an important mononuclear cell infiltrate in SO, MCP-1 and SDF-1 are candidate chemokines for investigation.…”
Section: Introductionmentioning
confidence: 99%